Engagement with a diverse Stakeholder Advisory Council for research in dementia care - Masoud, Sara S. (Res Involv Engagem, 2021)
BACKGROUND: The inclusion of stakeholders throughout the research process has been gaining recognition as an approach that can improve the quality and impact of research. Stakeholder engagement for dementia care research has been identified as a national priority, though evaluation of engagement strategies and their impact has been limited. In dementia care research, stakeholders can include individuals living with dementia, family care partners, and health and social care professionals in dementia care. A Stakeholder Advisory Council (SAC) was established to identify priorities for dementia care research that are most important to stakeholders. Strategies to build capacity for research and facilitate engagement among the SAC were used to identify the research priorities. This study describes the experiences of SAC members engaged in the research process. METHODS: To evaluate stakeholder engagement, semi-structured interviews were conducted with members of the SAC to understand their experiences and perspectives on the strategies used to facilitate engagement and build capacity for research. Interviews were recorded, transcribed, and thematically analyzed using a mixed inductive and deductive approach. Findings were presented to members of the SAC to determine whether they felt their perspectives and experiences were accurately represented. Final domains and themes presented here were approved by the SAC. RESULTS: Interviews (N = 11) were conducted with members of the SAC representing each stakeholder group; persons living with dementia (n = 2); family care partners (n = 4), and health and social care professionals in dementia care (n = 5). Ten themes were categorized into four overarching domains: accessibility, council infrastructure, values and environment, and benefits of involvement. CONCLUSIONS: Findings from this qualitative study are a resource for researchers seeking to collaborate with diverse stakeholder groups to represent their perspectives in research, including individuals living with dementia. The domains and themes identified here support the inclusion of diverse stakeholders in the research process, centering engagement and capacity building strategies around individuals living with dementia. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s40900-021-00297-8.